Research aim: To examine the determinants of consumer repurchase intention in shopping for Muslim fashion online. Methods: Explanatory research using the Structural Equation Modeling method with the SmartPLS3 program. Research Findings: The results show t - Bismala, Lila; Hasibuan, Lailan Safina; Handayani, Susi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: To examine the determinants of consumer repurchase intention in shopping for Muslim fashion online. Methods: Explanatory research using the Structural Equation Modeling method with the SmartPLS3 program. Research Findings: The results show that consumer satisfaction significantly affects consumer loyalty, which in turn mediates the relationship between consumer satisfaction and repurchase intention. E-WOM does not show a significant effect on repurchase intention either directly or through mediation. Theoretical Contribution: This study contributes to the e-commerce literature by revealing the relationship dynamics between consumer satisfaction, electronic word of mouth (e-WOM), customer loyalty, and repurchase intention on online platforms. Practical Implications: The results of this study provide strategic guidance for e-commerce business actors to increase customer loyalty as an important step in encouraging repeat purchases Research Limitations: This study is limited to the context of Muslim fashion online stores, so the results may not be generalizable to other products or different e-commerce platforms. Further research is needed to explore additional factors that can more comprehensively explain the relationship between consumer satisfaction and repurchase intention.